Pemanfaatan Media Tanam Daur Ulang untuk Vertikultur Sayuran dan Pengenalan Nama-Nama Sayuran dalam Bahasa Inggris - Nofan, Nofansyah; Ikhsan Maulana Irawan; Endah Tri Wahyuni; Rizky Ananda Pratama (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The community of Nipah-Nipah in Penajam Paser Utara faces challenges in optimizing limited land for household farming and managing household plastic waste, especially used bottles. To address these issues, a community service program was carried out by utilizing recycled planting media through verticulture farming and introducing vegetable names in English and Latin to enrich community knowledge. The program involved three academic disciplines: Management for activity planning and evaluation, English Literature for preparing educational stickers containing vegetable names in Indonesian, English, and Latin, and Engineering for designing and assembling verticulture racks. The method consisted of observation, preparation of materials, socialization, training, distribution, and monitoring. A total of 15 types of vegetables were planted in 120 recycled bottles, three verticulture racks were installed at the village office, and 50 planting packages were distributed to residents. The program successfully increased public awareness of environmentally friendly farming, reduced plastic waste, and improved plant literacy in English and Latin. Thus, the use of recycled planting media for vegetable verticulture is proven effective in optimizing narrow land, supporting sustainable agriculture, and strengthening community empowerment. Keywords: Verticulture; recycled planting media; vegetable literacy; sustainable farming; Nipah-Nipah